THE EFFECT OF A POLYDNAVIRUS OF APANTELES GALLERIAEON THE HEMOLYMPH PROTEINS OF HOST GALLERIA MELLONELA - Brochetto-braga, M.r. [UNESP]; Palma, M.s. [UNESP]; Ribeiro, J.c. [UNESP]; Gobbi, N. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 1995)
The presence of a polydnavirus in the ovary of the microhymenoptera Apanteles galleriae was detected. This wasp parasites the larvae of the wax moth Galleria mellonella. To study the possible viral effects on the total protein of G.mellonella, hemolymph extracts of the ovary calyxes of parasitized A. galleriae were injected into 6th and 7th instar cells of G.mellonella larvae. Protein profiles on polyacrilamide gel electrophoresis containing sodium dodecyl sulfate (SDS-PAGE) of host cell extracts showed a suppression of several protein bands when infection occurred in the 6th instar. However, in the 7th instar, parasitism caused an amplification in the synthesis of most proteins with some changes in the electrophoretic profile.
Keywords: microhymenoptera; wax moth; parasitism; polydnavirus; SDS-PAGE; Apanteles galleriae; Galleria mellonela